Principles and elements of interactive multimedia teaching aids design for hearing-impaired students - Aidah Alias; Azahar Harun; Norfadilah Kamaruddin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Interactive multimedia teaching aids are one of the effective tools for enhancing the learning experiences of students with disabilities. However, there is still a lack of evidence on the availability and appropriateness of such aids for hearing-impaired students. To address this issue, this study conducted a comprehensive contextual document review with a focus on a diverse range of scholarly sources, ensuring a robust foundation for the research through 31 established scholars. The primary objective is to identify the best principles and elements for designing effective interactive multimedia teaching aids that cater to the unique needs of hearing-impaired students. The analysis revealed 11 key principles, including clarity, multimedia, temporal contiguity, harmony, consistency, coherence, familiarity, spatial contiguity, embodiment, control, and contrast. The findings from this study provide valuable insights into the development of effective interactive multimedia teaching aids to fulfill the needs of hearing-impaired students, enabling them to receive a more inclusive and accessible education. More importantly, the findings represent vital guidance for educators, designers, and policymakers to create a more accessible learning environment for all students.